The Effect of Subjective Norm, Attitude, Product Price and Product Quality on Repurchase Intention of Skincare Brand Skintific - Yulisa Halim Wijaya; Margaretha Pink Berlianto (Dinasti Review, 2025)
The potential growth of the skincare industry in Indonesia makes Indonesia a competitive market, triggering manufacturers to strive to prevent customers from falling to other competitors. Retaining existing customers is the cheapest and easiest option for managers to take, because in a competitive industry it is quite difficult to acquire new customers. This study aims to examine the influence of subjective norms, attitudes, product prices and product quality on repurchase intentions. The study was conducted quantitatively on 262 users of Skintific products from workers working in Jabodetabek. The results showed that subjective norms, product prices and product quality were able to significantly and positively influence repurchase intentions, but product quality was not able to significantly influence repurchase intentions.